Advances in nanomaterial based approaches for enhanced fluoride and nitrate removal from contaminated water. Issue 13 (26th January 2016) - Suriyaraj, S. P.; Selvakumar, R.
Abstract : Various nanomaterials for fluoride and nitrate removal from contaminated water. Abstract : Fluoride and nitrate contamination in drinking water sources has been a major problem in many countries. The long term health hazards and increasing levels of fluoride and nitrate in drinking water through natural and anthropogenic sources are challenging and warrant the need for advanced technologies for abating these contaminants. Various technologies have been reported so far for fluoride and nitrate removal from drinking water. Recent advances in nanotechnology and nanomaterial synthesis have demonstrated significant impacts on fluoride and nitrate removal when compared to other conventional adsorbents and process. The present review discusses the recent advances in nanotechnology and nanomaterial synthesis, modification of process parameters and use of composite nanomaterials for enhanced removal of fluoride and nitrate from contaminated water.